Pulmonary Thromboembolism in a Case with Intracerebral Hemorrhage - Kirkil, Gamze; Deveci, Figen; Turgut, Teyfik; Turkoglu, Suat; Muz, Mehmet Hamdi (Aves, 2009)
Patients with intracerebral hemorrhage (ICH) who subsequently develop deep vein thrombosis (DVT) and/or pulmonary embolism (PE) present a difficult therapeutic dilemma. We herein report the therapy of PE in a case with ICH. A 46-year-old man with ICH after an hypertension attack underwent craniotomy for discharging the hematoma. After operation DVT occured on his left leg. On the 4th day of low molecular weight heparin therapy, respiratory distress appeared, and CT scan of thorax showed a thrombus on the distal segmentary branch of the left main pulmonary artery, so low dose unfractioned heparin (UFH) (5000 U tid) started. During follow period clinical and laboratory findings improved and the patient discharged by ordering anticoagulant therapy. Low dose UFH therapy can be an alternative in patients who develop PE after ICH.
Keywords: intracerebral hemorrhage; pulmonary thromboembolism; anticoagulant therapy